Comparative analysis of the results of treatment of trans- and suprasphincteric anal fistulae by thermo-obliteration of fistula track with diode laser or monopolar electrocoagulation - I. V. Kostarev (Вестник хирургии имени И.И. Грекова, 2020)
The objective of the study was to compare the results of two methods of thermo-obliteration of the fistula track by diode laser or monopolar electrocoagulation in patients with trans- and suprasphincteric anal fistulas.Methods and materials. 52 patients (men - 40, women - 12) were included in the study. 29 patients underwent laser coagulation (Laser group) and 23 patients underwent monopolar electrocoagulation (ME group) of fistula track combined with closure of internal fistula opening. Mean age of patients in Laser group was (46±13) years, in ME group - (41±12) years. In the Laser group, 11 (38 %) patients had suprasphincteric fistulae, and 18 (62 %) had transsphincteric fistulae passing through a superficial or deep portion of the external anal sphincter. In the ME group, 9 (39.1 %) patients had an suprasphincteric fistula and 14 (60.9 %) had a transsphincteric fistulae. The minimal period for assessing the healing rate was 2 months after surgery.Results. The average follow-up period after Laser was (9.5±3.0) (5-18) months, after ME - (12.2±7.3) (2-22) months. Primary healing of fistula in 2 months after surgery was 19/29 (65.5 %; 10 transsphincteric and 9 suprasphincteric fistulas) in the Laser group versus 7/23 (30.4 %; 5 transsphincteric and 1 suprasphincteric fistulas) in the ME group (p<0.05). There were no cases of fecal incontinence development after laser or monopolar coagulation of fistula track.Conclusion. A comparative analysis of the first results showed that although in both groups, after thermo-obliteration of the fistula track, the frequency of non-healing of fistula exceeds 30 %, in the group where a diode laser was used, the results were statistically significantly better compared to the group of monopolar electrocoagulation (65.5 against 30.4 %).